Importancia de la coordinación motora gruesa de niños de 4 años de la Institución Educativa N°1685, Trujillo - 2020 - Díaz Romero, Yurico Margarita (2022)
The present basic research entitled Importance of gross motor coordination of 4-year-old children of the Educational Institution N ° 1685, Trujillo - 2020, aimed to analyze the importance of gross motor coordination of 4-year-old children of the Educational Institution N ° 1685, Trujillo - 2020. The research design was of a basic type of simple descriptive design, with a population of 133 boys and girls aged 3, 4 and 5 years from the Educational Institution No. 1685 María Inmaculada and a sample of 24 boys and girls from the 4-year-old classroom of the Educational Institution in question. The survey technique was used and a questionnaire was used as an instrument to collect information on gross motor coordination. The results obtained show us that the level of gross motor coordination in children is at a low level, which means that the child needs movement in the open air to be able to function and interact with others, that is why it is required at this stage to raise psychomotor activities that develop their level of gross motor coordination as it helps in their personal development.